Health plan‐based mailed fecal testing for colorectal cancer screening among dual‐eligible Medicaid/Medicare enrollees: Outcomes of 2 program models. Issue 2 (29th September 2021) - Baldwin, Laura‐Mae; Coronado, Gloria D.; West, Imara I.; Schwartz, Malaika R.; Meenan, Richard T.; Vollmer, William M.; Petrik, Amanda F.; Shapiro, Jean A.; Kulkarni‐Sharma, Yogini R.; Green, Beverly B.
Abstract : Background: Health insurance plans are increasingly offering mailed fecal immunochemical test (FIT) programs for colorectal cancer (CRC) screening, but few studies have compared the outcomes of different program models (eg, invitation strategies). Methods: This study compares the outcomes of 2 health plan–based mailed FIT program models. In the first program (2016), FIT kits were mailed to all eligible enrollees; in the second program (2018), FIT kits were mailed only to enrollees who opted in after an outreach phone call. Participants in this observational study included dual‐eligible Medicaid/Medicare enrollees who were aged 50 to 75 years and were due for CRC screening (1799 in 2016 and 1906 in 2018). Six‐month FIT completion rates, implementation outcomes (eg, mailed FITs sent and reminders attempted), and program‐related health plan costs for each program are described. Results: All 1799 individuals in 2016 were sent an introductory letter and a FIT kit. In 2018, all 1906 were sent an introductory letter, and 1905 received at least 1 opt‐in call attempt, with 410 (21.5%) sent a FIT. The FIT completion rate was 16.2% (292 of 1799 [95% CI, 14.5%‐17.9%]) in 2016 and 14.6% (278 of 1906 [95% CI, 13.0%‐16.2%]) in 2018 ( P = .36). The overall implementation costs were higher in 2016 ($40, 156) than 2018 ($34, 899), with the cost per completed FIT slightly higher in 2016 ($138) than 2018 ($126). Conclusions: An opt‐in mailed FIT program achieved FIT completion rates similar to those of a program mailing to all dual‐eligible Medicaid/Medicare enrollees. Lay Summary: Health insurance plans can use different program models to successfully mail fecal test kits for colorectal cancer screening to dual‐eligible Medicaid/Medicare enrollees, with nearly 1 in 6 enrollees completing fecal testing. Abstract : In this study, a health insurance plan demonstrates its ability to deliver 2 different mailed fecal immunochemical test (FIT) program models, with vendors used to manage some program elements. These mailed FIT programs began to close gaps in colorectal cancer screening rates in the health plan's dual‐eligible Medicaid/Medicare population.